Insight into Canary Island pine physiology provided by stable isotope patterns of water and plant tissues along an altitudinal gradient - Miranda, José Carlos; Lehmann, Marco M; Saurer, Matthias; Altman, Jan; Treydte, Kerstin (Tree physiology, 2021)
The Canary Islands, an archipelago east of Morocco's Atlantic coast, present steep altitudinal gradients covering various climatic zones from hot deserts to subalpine Mediterranean, passing through fog-influenced cloud forests. Unlike the majority of the Canarian flora, Pinus canariensis C. Sm. ex DC. in Buch grow along most of these gradients, allowing the study of plant functioning in contrasting ecosystems. Here we assess the water sources (precipitation, fog) of P. canariensis and its physiological behavior in its different natural environments. We analyzed carbon and oxygen isotope ratios of water and organics from atmosphere, soil and different plant organs and tissues (including 10-year annual time series of tree-ring cellulose) of six sites from 480 to 1990 m above sea level on the Canary Island La Palma. We found a decreasing δ18O trend in source water that was overridden by an increasing δ18O trend in needle water, leaf assimilates and tree-ring cellulose with increasing altitude, suggesting site-specific tree physiological responses to relative humidity. Fog-influenced and fog-free sites showed similar δ13C values, suggesting photosynthetic activity to be limited by stomatal closure and irradiance at certain periods. In addition, we observed an 18O-depletion (fog-free and timberline sites) and 13C-depletion (fog-influenced and fog-free sites) in latewood compared with earlywood caused by seasonal differences in: (i) water uptake (i.e., deeper ground water during summer drought, fog water frequency and interception) and (ii) meteorological conditions (stem radial growth and latewood δ18O correlated with winter precipitation). In addition, we found evidence for foliar water uptake and strong isotopic gradients along the pine needle axis in water and assimilates. These gradients are likely the reason for an unexpected underestimation of pine needle water δ18O when applying standard leaf water δ18O models. Our results indicate that soil water availability and air humidity conditions are the main drivers of the physiological behavior of pine along the Canary Island's altitudinal gradients.
Keywords: Oxygen Isotopes; stromy; ekosystém; voda; Španělsko; Ecosystem; Carbon Isotopes; Water; izotopy uhlíku; Trees; Spain; izotopy kyslíku; borovice; Pinus